Strength Optimization of Spot Resistance Welded A.H.S.S Dissimilar Thickness by Taguchi Method - Khaled Marwan; Mohamed Aljadi; Maryam Morgham; Mohammed Ammar Abuqunaydah (African Journal of Advanced Pure and Applied Sciences, 2026)
This study investigates the spot resistance spot welding (SRW) of dissimilar thickness TRIP800 and DP600 steels, which belong to the advanced high strength steel (AHSS) group. Various welding parameters were applied to join these steels, and the optimal weldment strength was targeted through a systematic optimization using the Taguchi method. Tensile shear tests were performed to evaluate the weldment’s strength and energy absorption under different welding conditions, which were determined based on the Taguchi L9 orthogonal array design. The results of the optimization process were analyzed using the "the better is the best" approach, with evaluations based on averaging the experimental data. The analysis revealed that welding time is the most significant parameter influencing both weld strength and energy absorption in the dissimilar thickness steels. The welding parameter set that yielded the highest strength, identified by the Taguchi method, closely matched the actual strength values obtained through experimental tests.